Non-Injection Chemotherapy Regimens for Drug Resistant Tuberculosis in Children and Adolescents - V. A. Aksenova; N. I. Klevno; A. V. Kazakov; A. D. Pakhlavonova; V. A. Romanenko; N. Yu. Nikolenko (Туберкулез и болезни лёгких)
The objective: to determine the effectiveness and safety (tolerability) of non-injection chemotherapy regimens containing bedaquiline in pediatric patients with multiple drug resistant respiratory tuberculosis.Subjects and Methods. Effectiveness and safety of treatment regimens containing non-injection drugs and Bdq were studied in 45 children from Main Group (MG) aged from 5 to 17 years old inclusive who were ill with multiple drug resistant tuberculosis. Control Group (CG) included patients of the same age with MDR TB who were treated with chemotherapy regimens containing injectable drugs (a retrospective study).Results. After 24 weeks (the period during which patients took bedaquiline), clinical effectiveness of chemotherapy regimens was achieved in all patients. By the end of week 24 of treatment, significant positive radiographic changes were noted in 84.4% of  patients in MG and in 75.7% in CG (OR 1.741; 95% CI 0.658–4.611), healing of cavities was achieved in 42 (93.3%) and 66 (94.3%) patients, respectively (OR 0.848, 95% CI 0.181-3.982). No tuberculous mycobacteria were not detected in 100% of cases in both groups by month 6 of chemotherapy. The number of adverse reactions (AR) per patient averaged 1.25 and 1.26 in MG and CG. ARs occurred in patients receiving aminoglycosides in 41.4%: in MG – in 33.3%; 4/70 (5.7%) children from CG receiving injectable drugs developed adverse reactions requiring replacement of anti-tuberculosis drugs. No irreversible ARs were observed in MG.